The Routledge handbook of philosophy of disagreement - Baghramian, Maria; Carter, J. Adam, 1980-; Cosker-Rowland, Rach (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"Disagreement is one of the deepest and most pervasive topics in philosophy, arguably its very bedrock, and is an ever-increasing feature of politics, ethics, public policy, science and many other areas. Despite the omnipresence of disagreement, the topic itself has received relatively little sustained examination. In this outstanding handbook a team of international contributors examines the philosophy of disagreement and how it extends to debates in public policy and science. Comprising forty-one chapters by an international team of contributors, the Handbook is divided into six clear parts: Philosophy of Disagreement Epistemology of Disagreement Disagreement about Science Moral Disagreement Disagreement in Politics Disagreement in Public Policy Within these sections key topics are examined, including: skepticism, truth, pluralism, feminist philosophy, experimental philosophy, epistemology of peer disagreement, rationality, intellectual virtue, relativism, realism, instrumentalism, scientific method and perspectivism. Ideal for those studying and researching philosophy, especially epistemology, ethics and philosophy of science, this handbook will also be of interest to those in related disciplines such as politics, social policy, and law"--
Philosophy of disagreement -- Varieties of disagreement / Steven D. Hales -- What's the point? Championing a view under conditions of philosophical disagreement / Sanford C. Goldberg.
Keywords: Compromise (Ethics); Conflict management; Debates and debating; Toleration; PHILOSOPHY / General